Kaji Eksperimental Pengaruh Temperatur Pada Campuran Bahan Bakar Biosolar Dan Ethanol Untuk Kinerja Mesin Diesel Dong Feng - Hendinto Simanihuruk; Romy Romy; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Biodiesel fuel and ethanol are fuels that have been used in diesel engines. In this study, the focus was on the effect of temperature on a mixture of biodiesel fuel and ethanol on the performance of diesel engines, Feng to be used as an electric generator. The test equipment used is a dong Feng diesel engine in the University of Riau mechanical engineering laboratory. Testing of diesel engines is carried out with constant rotation and constant voltage. Comparison of fuel mixtures used Biosolar (B20) 95% with 5% ethanol, Biosolar (B20) 90% with 10% ethanol and Biosolar (B20) 85% with 15% ethanol in 1000 ml with variations in temperatures of 50oC, 60oC and 70oC and loading 1000 watts, 2000 watts and 3000 watts. The results showed that the performance of the Dong Feng diesel engine for using electric generators with biodiesel 95% and 5% ethanol in 1000 ml increased the effective power, torque and brake mean effective pressure by 5.88% compared to only using biodiesel. The effect temperature on the mixture and biosolar and ethanol fuel are fuel consumption, thermal efficiency and air and fuel ratio in the biodiesel mixture of B20 95% and 5% ethanol with a temperature of 60oC which increased 5.06% compared to biodiesel. But the increase in effective power, torque and speed increased.Key word : diesel engine, biosolar, ethanol, temperature, viskosity